Feeling present in the work relationships of nursing: the envy - Pradebon, Vania Marta; Erdmann, Alacoque Lorenzini (Rev Rene, 2002)
This article is about the envy feeling, its concepts, origin and characteristics, as well as its presence in the work relationship of nursing organizations. An opinion poll states that hospital instituitions with nursing professionals, the characteristics of envied and envious and implications on work relationship. To start the discussion about the importance of the topec and about the unknowledge of itself.